Exploring the Role of Social Media in Adolescence Ecology - Arora, Chetna; Chander, Subhash (Indian Journal of Educational Technology, 2024)
A qualitative study was conducted in Delhi/NCR to understand the role of social media in adolescence ecology. The objectives of the study were to study the change in parenting and teaching styles due to social media, to explore the usage of social networking sites among adolescents and to explore the positive and negative aspects of social media and how it impacts adolescents/students. For the same, research was conducted across adolescents in the age group of 15-19 (questionnaire), few teachers (detailed interviews) and few parents (detailed interviews). The key findings highlighted that most adolescents find that social media has positive effects on their lives as it helps them academically, maintains social relationships and is a good leisure activity. Most parents think that social media has helped their children in their studies owing to YouTube educational channels and quite a few educational sites. Teachers had mixed opinions on social media usage with the preference being given to conventional classrooms, but they do agree it helps to motivate students. One flip side being observed is the rigour of doing research is reducing among students as social media becomes the norm for research.